2015
DOI: 10.1038/onc.2015.263
|View full text |Cite
|
Sign up to set email alerts
|

KLF5 promotes breast cancer proliferation, migration and invasion in part by upregulating the transcription of TNFAIP2

Abstract: The Kruppel-like factor 5 (KLF5) transcription factor is highly expressed in high-grade and basal-like breast cancers. However, the mechanism by which KLF5 promotes cell migration and invasion is still not completely understood. In this study, we demonstrate that TNFAIP2, a tumor necrosis factor-α (TNFα)-induced gene, is a direct KLF5 target gene. The expression of TNFAIP2 is highly correlated with the expression of KLF5 in breast cancers. The manipulation of KLF5 expression positively alters TNFAIP2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 50 publications
6
148
1
Order By: Relevance
“…Because it has been suggested that several cancer-promoting genes, such as Akt [38], c-Myc [32], KLF5 [33], and DRD2 [34] are involved in cell survival or proliferation in BCa cells, we sought to compare the status of these genes in human TNBC tumors versus non-TNBC tumors. Thus, we analyzed the gene amplification and mRNA copy number gain (amplification/gain) data available from The Cancer Genome Atlas (TCGA) datasets using cBioPortal [39, 40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it has been suggested that several cancer-promoting genes, such as Akt [38], c-Myc [32], KLF5 [33], and DRD2 [34] are involved in cell survival or proliferation in BCa cells, we sought to compare the status of these genes in human TNBC tumors versus non-TNBC tumors. Thus, we analyzed the gene amplification and mRNA copy number gain (amplification/gain) data available from The Cancer Genome Atlas (TCGA) datasets using cBioPortal [39, 40].…”
Section: Resultsmentioning
confidence: 99%
“…Activation of FOXO3 tumor suppressor by TFP or BPD is a significant distinction from traditional antipsychotic inhibitors and the resultant downregulation of oncogenic survival factors, c-Myc [32] and Kruppel-like factor 5 (KLF5) [33], in TNBC is an interesting anticancer mechanism. Unexpectedly, we uncover that both TFP and BPD display suppression of the expression of the dopamine receptor D2 (DRD2), which has been suggested as a key receptor for selective-targeting cancer stem cells (CSC) [34], in a FOXO3-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…6D). COMMD7 (You et al ., 2017), ITGA1 (Boudjadi et al ., 2013; Gulubova, 2004; Schadendorf et al ., 1996), RAB3D (Luo et al ., 2016; Yang et al ., 2003), and TNFAIP2 (Chen et al ., 2011; Jia et al ., 2016) have all been shown to be upregulated in various cancers including PDAC. While we cannot assume these changes will be universal in all PDAC samples, this consistency suggests that some of these genes could make promising targets or biomarkers for APE1‐based therapy or combination therapies that potentially will be useful across multiple PDAC tumor subtypes and in other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…For Re-ChIP, the primary ChIP material was released from the agaroses and subjected to second round of immunoprecipitation using corresponding Abs. For chromatin immunodepletion (ChID), ChIP material isolated from the agaroses was immunoprecipitated again with an anti-Ac-K Ab, and GDF15 promoter fragment in the supernatant immunodepleted with anti-Ac-K was detected [15, 27]. The primers for GDF15 promoter fragments were as follows: primer for −234 to −76 nt, forward: 5′-GGCTGGAATGGTGTCCT-3′, reverse: 5′-CCCCTGCCTGCAGAGTA-3′; primer for −103 to +58, forward: 5′-TCAAACAATCCACCCACCT-3′, reverse: 5′-TTTCCAGTCTAAGCAGGGTG-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Reportedly, kruppel-like factor 5 (KLF5), as a transcription factor, can boost breast cancer cell proliferation [15], and activate sox4 or HIF-1α transcription via binding to GC-rich DNA sequences, resulting in lung cancer proliferation [16]. Moreover, as a transcriptional co-activator, general control non-depressible (GCN5) potentiates NSCLC growth by increasing E2F1 and cyclin D1 expression [17] and accelerates glioma development as well [18].…”
Section: Introductionmentioning
confidence: 99%